Anti-Myxovirus Resistance Protein-1 Immunoglobulin A Autoantibody in Idiopathic Pulmonary Fibrosis. (29th March 2022) - Arai, Toru; Hirose, Masaki; Hamano, Yoshimasa; Kagawa, Tomoko; Murakami, Akihiro; Kida, Hiroshi; Kumanogoh, Atsushi; Inoue, Yoshikazu
Abstract : Background . We have previously analysed serum autoantibody levels in patients with idiopathic pulmonary fibrosis (IPF), idiopathic nonspecific interstitial pneumonia (iNSIP), and healthy controls and identified the autoantibody against anti-myxovirus resistance protein-1 (MX1) to be a specific autoantibody in iNSIP. We found that a higher anti-MX1 autoantibody level was a significant predictor of a good prognosis in patients with non-IPF idiopathic interstitial pneumonias. In this retrospective study, we sought to clarify the prognostic significance of the anti-MX1 autoantibody in IPF. Methods . We measured anti-MX1 immunoglobulin (Ig) G, IgA, and IgM autoantibody levels by enzyme-linked immunosorbent assay in serum collected at the time of diagnosis from 71 patients with IPF diagnosed according to the 2018 IPF guideline. The gender-age-physiology (GAP) index was calculated in each case. Results . The study population (59 men and 12 women) had a median age of 67 years. Serum anti-MX1 IgG and IgA autoantibody levels correlated positively with GAP stage (p < 0.05 ). Univariate Cox proportional hazards regression analysis did not identify an elevated anti-MX1 IgG, IgA, or IgM autoantibody level as a significant prognostic factor; however, a higher anti-MX1 IgA autoantibody level heralded significantly poorer survival after adjustment for GAP stage (p = 0.030 ) and for percent forced vital capacity and modified Medical Research Council score (p = 0.018 ). Neither the anti-MX1 IgG autoantibody nor the IgM autoantibody could predict survival after these adjustments. Conclusions . The serum anti-MX1 IgA autoantibody level is a significant prognostic factor in IPF. Further studies are needed to clarify the pathophysiological role of this autoantibody in IPF.